The Rise of China as a Hegemonic Power: The Case for a Partial Peaceful Rise - Bin Huwaidin, Mohamed; Antwi-Boateng, Osman (Journal of Regional Security, 2021)
China’s rise is a significant concern for international security. It is essential to understand the trajectory of China’s rise in order to determine world safety and prosperity measures in a period of great uncertainty. This study provides an overview of the two main possible security consequences of China’s rise, that is, a peaceful rise and a warlike rise, by surveying arguments found in the literature regarding both aspects. The research extends beyond the often-made binary argument of “peaceful rise versus non-peaceful rise” since aspects of both arguments can explain the country’s rise. This research offers a nuanced assessment of China’s rise by positing a partial peaceful rise explanation whereby China seeks a non-confrontational way of asserting itself globally vis-a-vis the United States, while at the same time, modernizing and expanding its military capabilities in preparation for any eventualities.
Keywords: power transition theory; China's rise; partial peaceful rise; Sino-US relations; international security